Development of Tourism in Kerinci Regency Based on E-Tourism to Enhance Tourist Decision-Making and Drive Regional Economic Growth - Lestari, Anggia Ayu; Efrianto, Efrianto (Yayasan Riset dan Pengembangan Intelektual, 2025)
To establish Kerinci Regency as a premier tourist destination, a strategic development model is essential. This study aims to develop a tourism promotion model utilizing digital platforms such as websites, social media, and other online tools to enhance accessibility and visibility for tourists. Using the Quantitative Strategic Planning Matrix (QSPM) method, supported by the IE Matrix and SWOT analysis, data were collected through Focus Group Discussions (FGDs) involving key stakeholders and tourists. The analysis results indicate that the IE Matrix places the development strategy in quadrant I (Growth and Build), highlighting the need for an aggressive strategy. The QSPM analysis identifies the top-priority strategy as leveraging technology to expand promotional outreach. This approach emphasizes the critical role of e-tourism in driving tourism growth and supporting regional economic development.